Acceptability of DNA as Evidence in Child Denial (Li'ān) Cases at Bangil Religious Court - Diana Azzahra (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Under Islamic law, li'ān is a judicially supervised oath procedure allowing a husband to deny a child's lineage when he cannot produce four witnesses to substantiate an adultery accusation. Although the Compilation of Islamic Law (KHI) regulates li'ān without referencing DNA evidence, judges at Bangil Religious Court have informally required DNA testing before accepting child denial filings, creating a normative gap between codified procedure and field practice. This study describes the use of DNA testing as evidence in li'ān child denial filings from the perspective of fiqh and legislation, and analyzes Bangil Religious Court judges' views on the evidentiary position of DNA results in deciding li'ān cases. Employing an empirical juridical method with a qualitative approach, primary data were gathered through semi-structured interviews with three judges selected via snowball sampling, supplemented by statutory instruments, fiqh literature, and fatwa documents, analyzed through editing, classification, verification, analysis, and conclusion-drawing stages. Classical fiqh and five major fatwa institutions converge in treating DNA as corroborative evidence (qarīnah) rather than a substitute for the li'ān oath. The three judges diverge: two consider valid DNA results sufficient to dispense with the oath, while one regards DNA as supplementary, becoming primary only when witnesses are unavailable—a position this study finds most doctrinally defensible. A granted li'ān ruling severs the child's lineage solely to the mother. The study recommends a Supreme Court circular letter and subsidy schemes to reconcile DNA-based proof with the principle of simple, fast, and low-cost justice.